IMPROVEMENT OF SYSTEM CERTIFICATION OF ORGANIC AGRARIAN PRODUCTION IN UKRAINE - HONCHARENKO, Nataliia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the actual problem of forming a certification system for organic production of agricultural products. It was determined that for the successful development of organic production, certification is of decisive importance, as it is a tool for protecting the rights of consumers and conscientious producers. It is noted that a clearly formed system of standardization and certification of organic production of agricultural products has not been implemented in Ukraine yet. This complicates the development of the organic sector, reduces the competitiveness of domestic producers on the international and national markets. It was established that, taking into account the export orientation, it is proposed to apply the public-private model of the organic production certification system. It has been proven that in modern conditions such a model has critical drawbacks for the domestic organic sector: duplication and irrational distribution of accreditation and state supervision functions between state authorities, the growth of corruption risks, the creation of obstacles to competition on the market of certification services, the complexity of implementation in the conditions of budgetary limitations financing. It is proposed to improve the proposed public-private model of the organic production certification system by creating a collegial non-governmental authority — the Accreditation Commission of Organic Production. The reduction of state regulation will contribute to the rapid formation of the certification system, the growth of competition in the certification services market, and the improvement of regulatory and institutional support for certification for domestic stakeholders.